Pengaruh Laju Pengadukan Dalam Pembuatan Bioetanol Dari Limbah Serabut Buah Sawit Menggunakan Saccharomyces cerevisiae - Muria, Sri Rezeki; Jeckson, Edie; Ahmad, Adrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The development of new and renewable energy resources of government’s strategies to reduce CO2 emission from industry waste and declining for national dependence of oil fuel. One of alternative energy that use to substitute a fuel oil is bioethanol. Palm fruit fibre waste is the one of potential source because of the biggest feedstock in Indonesia and the less uses that waste well. Some of type process used to convert bioethanol from industry waste, such as fermentation. The purpose of this experiment is decide the effect of fermentation in bioethanol production from palm fruit fibre waste to get an optimum bioethanol product. This experiment had pretreatments like delignification with ash extract palm fruit bunch and purification with H2O2 3% that were used to remove lignin in palm fruit fibre waste compound to get a lot of cellulose compound. The fermentation that use in this experiment is Separate Hydrolysis Fermentation (SHF) which is hydrolysis and fermentation done separately. Hydrolysis process using H2SO4 2 M for convert cellulose become glucose then will be done by anaerob fermentation by Saccharomyces cerevisiae. The variation of agitation speed (100, 150, 200, and 250 rpm) while fermentation learned to get an optimum bioethanol percentage. The result of experiment showed that in agitation speed at 200 rpm while 96 hours can convert a bioethanol 5 % (v/v) 39,465 g/L.Keywords: Agitation speed, bioethanol, delignification, Saccharomyces cerevisiae, palm fruit fibre waste, purification, SHF (Separate Hydrolysis Fermentation)